Chemical diversification of angucycline natural products: heterologous expression of lugdunomycin tailoring genes - Antin, Sofia (My University, 2025)
Antimicrobial resistance is a quickly growing threat with a huge global impact. Majority of antibiotics have been sourced from soil-dwelling Streptomyces bacteria, which are naturally tremendous at producing broad-spectrum antibiotics, such as kanamycin and streptomycin. Still, their potential as antimicrobial compound producing organisms is to be fully harnessed. According to genomic mining studies, Streptomyces is known to have the ability to produce numerous unknown secondary metabolites with potential bioactivity. Polyketides are the largest group of secondary metabolites produced by Streptomyces. Several polyketides, such as tetracycline and erythromycin, are in wide clinical use as, for example, antibacterials, antitumor agents, and antifungals. Angucyclines are a large and diverse group of aromatic polyketides distinguished by their unique bent four-ring benz[a]anthraquinone scaffold. Lugdunomycin is an angucycline-derived secondary metabolite. It has gained great interest due to its unique structure and elusive biosynthetic pathway. Lugdunomycin represents a novel subclass of aromatic polyketides that have undergone cleavage of the C-ring, leading to drastic and complex structural arrangements. The lugdunomycin pathway is still to be fully characterized, as the biosynthesis requires multiple complex steps. The aim of this study was to construct the pathway step by step using the BioBricks method for heterologous expression in Streptomyces. Thus, a library consisting of single gene building blocks could be established. Producing the pathway intermediates for enzymatic assays provides essential information about the mechanism of the biosynthesis. Understanding the pathway is of great importance as it would greatly benefit designing novel synthetic antibiotic structures.
Keywords: antibiotic, Streptomyces, polyketides, angucyclines, lugdunomycin